Sarcopenia, sarcopenic obesity, and arterial stiffness among older adults - Fantin, Francesco; Giani, Anna; Manzato, Gisella; Zampieri, Annachiara; Comellato, Gabriele; Urbani, Silvia; Zoico, Elena; Mazzali, Gloria; Zamboni, Mauro (Frontiers in Cardiovascular Medicine, 2024)
Background: Aging is associated to higher prevalence of sarcopenia and sarcopenic obesity (SO) and to increased arterial stiffening, with possible detrimental effects on morbidity and mortality. Aim of this study was to assess the relationships between sarcopenia, SO and different indexes of arterial stiffness in older adults. Methods: 77 hospitalized patients (mean age 78.68 ±9.65 years) were evaluated, obtaining anthropometric variables, biochemical samples, handgrip test and body composition assessment. Arterial stiffness was evaluated measuring both carotid-femoral pulse wave velocity (cfPWV), proxy for central stiffness, and cardio-ankle vascular index (CAVI), also considering peripheral arteries. The population was sorted into four subgroups: obese, sarcopenic, SO and controls. Results: The highest CAVI (11.31±2.58) was found in sarcopenic patients. SO had the highest value of cfPWV (15.18±8.44m/s), even after adjustment for significant covariates. In multiple regressions, SO diagnosis resulted a significant predictor of cfPWV, (p 0.03, R 2 0.20); sarcopenia diagnosis resulted predictor of CAVI (p 0.042, R 2 0.12). Conclusions: In conclusion, a positive correlation is found between sarcopenia, SO and arterial stiffness among older subjects. In particular, greater central arterial stiffness is associated to SO, outlining remarkable effect on the cardiovascular risk profile.